The Application of Morning Routine for Patients with Critical Illness in Intensive Care Units: A Case Report - Massie, Juliana G.E.P; Waluyo, Agung; Putra, Kharisma Adytama (Jurusan Keperawatan FIKES UNSOED, 2021)
Respiratory failure is still the main cause of morbidity and mortality at the Intensive Care Unit. One of the abnormalities in the respiratory system that can cause respiratory failure is Acute Respiratory Distress Syndrome (ARDS). This condition is a respiratory emergency characterized by a progressive decrease in oxygen after a serious illness or injury. Critical illness and treatment in the Intensive Care Unit are a less pleasant experience for patients and affect the patients’ psychologies. The unstable psychical conditions of the patients during the treatments also influence the physical condition of the patients and it affected to the length of the stay, the risk for complications, and nosocomial infections. Patients’ ability to be adapted to the intensive care environment is one of the keys to the success of the nursing care for the critical cases. The purpose of this study is to describe the comprehensive and holistic nursing care management in ARDS cases at the Intensive Care Unit. One of the focuses of the nursing interventions, in this study, is the environmental and intensive care atmosphere modifications of the intensive care unit called the morning routine.